Identifying the current and future status of freshwater connectivity corridors in the Amazon Basin - Bernardo Caldas; Michele L. Thieme; Natalie Shahbol; Maria E. Coelho; Guenther Grill; Paul A. Van Damme; Ricardo Aranha; Carlos Cañas; Camila K. Fagundes; Nicole Franco‐León; Edgar E. Herrera‐Collazos; Céline Jézéquel; et al. (Conservation Science and Practice, 2023)
Abstract The Amazon Basin features a vast network of healthy, free‐flowing rivers, which provides habitat for the most biodiverse freshwater fauna of any basin globally. However, existing and future infrastructure developments, including dams, threaten its integrity by diminishing river connectivity, altering flows, or changing sediment regimes, which can impact freshwater species. In this study, we assess critical rivers that need to be maintained as freshwater connectivity corridors (FCCs) for selective freshwater species—long‐distance migratory fishes and turtles (both with migrations >500 km) and river dolphins. We define FCCs as river stretches of uninterrupted river connectivity that provide important riverine and floodplain habitat for long‐distance migratory and other species and that maintain associated ecosystem functions. We assessed more than 340,000 km of river, beginning with an assessment of the connectivity status of all rivers and then combining river status with models of occurrence of key species to map where FCCs occur and how they could be affected under a scenario of proposed dams. We identified that in 2019, 16 of 26 very long (>1000 km) rivers are free‐flowing but only 9 would remain free‐flowing if all proposed dams are built. Among long and very long rivers (>500 km), 93 are considered FCCs. Under the future scenario, one‐fifth (18) of these long and very long FCCs—those that are of critical importance for long‐distance migrants and dolphins—would lose their FCC status, including the Amazon, the Negro, Marañón, Napo, Ucayali, Preto do Igapó Açu, Beni, and Uraricoera rivers. To avoid impacts of poorly sited infrastructure, we advocate for energy and water resources planning at the basin scale that evaluates alternative development options and limits development that will impact on FCCs. The results also highlight where corridors could be designated as protected from future fragmentation.